Model Conceptual Understanding Procedures (CUPs): Implementasinya dalam Mengatasi Miskonsepsi Matematis Siswa - Maulidiya; Hafriani; Firhat; Rizal, Muhammad (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
Misconceptions are a misunderstanding between the concepts that students understand and the actual concepts. The reality in the field shows that students' mathematical misconceptions often occur, so a model is needed that can overcome them, namely using the Conceptual Understanding Procedures (CUPs) learning model. This research aims to find out whether the Conceptual Understanding Procedures (CUPs) learning model can overcome high school students' mathematical misconceptions. This research uses a quasi-experimental research method with a pretest-posttest design. The sample is class XI MIA 2. The research instrument uses a description test sheet. Data analysis used statistical tests, namely paired sample t-test, which obtained t_count>t_tabel= 23.55>1.72 so that H1 was accepted, which means the Conceptual Understanding Procedures (CUPs) learning model can significantly overcome mathematical misconceptions students.